2014
DOI: 10.1530/rep-13-0522
|View full text |Cite
|
Sign up to set email alerts
|

Human urinary excretion of non-persistent environmental chemicals: an overview of Danish data collected between 2006 and 2012

Abstract: Several non-persistent industrial chemicals have shown endocrine disrupting effects in animal studies and are suspected to be involved in human reproductive disorders. Among the non-persistent chemicals that have been discussed intensively during the past years are phthalates, bisphenol A (BPA), triclosan (TCS), and parabens because of their anti-androgenic and/or estrogenic effects. Phthalates are plasticizers used in numerous industrial products. Bisphenol A is the main component of polycarbonate plastics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
100
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(122 citation statements)
references
References 58 publications
13
100
9
Order By: Relevance
“…In addition, high-MWP (as the sum of molar concentrations of MEHP, MEHHP, MEOHP, MHiNP, MOiNP and MOP) and low-MWP (as the sum of molar concentrations of MEP, MiBP, MnBP, OH-MnBP and MBzP) were calculated. The selected phthalate metabolites were similar as in other studies and indicated the proxy of exposure to different types of products [1,12,[19][20][21][22].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In addition, high-MWP (as the sum of molar concentrations of MEHP, MEHHP, MEOHP, MHiNP, MOiNP and MOP) and low-MWP (as the sum of molar concentrations of MEP, MiBP, MnBP, OH-MnBP and MBzP) were calculated. The selected phthalate metabolites were similar as in other studies and indicated the proxy of exposure to different types of products [1,12,[19][20][21][22].…”
Section: Discussionsupporting
confidence: 80%
“…Levels of most of the phthalate metabolites detected in the urine of pregnant women in Poland were in an order of magnitude similar to that observed among pregnant women in Denmark [27]. It is important to note that MEP levels were much lower in Poland (as well as in Denmark and Japan) compared to those observed in Spain, France, the Netherlands and US [10][11][12][27][28][29]. In addition, MBzP was detected only in 49% of Polish samples, which is similar to the results observed in Denmark (MBzP > LOD in 69% of the samples) but lower metabolites.…”
Section: Exposure Assessmentsupporting
confidence: 75%
See 3 more Smart Citations